Neuromuscular electrical stimulation as an adjunct to endurance and resistance training during pulmonary rehabilitation in stable chronic obstructive pulmonary disease. (August 2015) - Tasdemir, Filiz; Inal-Ince, Deniz; Ergun, Pinar; Kaymaz, Dicle; Demir, Nese; Demirci, Ebru; Egesel, Nurcan
<x xml:space="preserve">Abstract</x> Aim: The purpose of this study was to investigate whether adding neuromuscular electrical stimulation (NMES) to a comprehensive pulmonary rehabilitation (cPR) program would have additive effects on clinical-functional outcomes. Methods: Twenty-seven chronic obstructive pulmonary disease patients participating in a 10-week cPR program were randomly allocated to NMES + cPR (n = 13) or Sham + cPR (n = 14) groups. Quadriceps strength, exercise capacity, symptoms, mood, activities of daily living and quality of life were evaluated pre- and post-interventions. Results: There were no significant differences in any of the physiological and subjective improvements induced by NMES + cPR versus Sham + cPR (p > 0.05). In fact, the NMES + cPR group showed lower increases in incremental shuttle walk test (ISWT) distance (38.4 vs 69.2 m, respectively) and %ISWT distance (5.1 vs 9%, respectively) compared with the Sham + cPR group (p < 0.05). Conclusion: The increase in exercise capacity is less important when NMES is used as an adjunct to the cPR.